The Discipline of International Law in Republican China and Contemporary Taiwan - Pasha L. Hsieh (Washington University Global Studies Law Review, 2015)
This Article examines the evolution of international law as a professional and intellectual discipline in the Republic of China (ROC), which has governed Mainland China (1912–1949) and post-1949 Taiwan. The ROC’s centennial development fundamentally shaped modern China’s course of foreign relations and postwar global governance. The Article argues that statism, pragmatism, and idealism define the major features of the ROC’s approach to international law. These characteristics transformed the law of nations into universally valid normative claims and prompted modern China’s intellectual focus on the civilized nation concept. First, the Article analyzes the professionalization of the discipline of international law. It offers insight into the cultivation of China’s first-generation international lawyers in the Foreign Ministry, international law societies, and the Shanghai Mixed Court. Second, it explores the ROC’s approach of assertive legalism in applying international law to advance diplomatic objectives. The nation’s strategic engagement with unequal treaties, the League of Nations, and the United Nations contributed to its Grotian moment. The assertion of legal claims in judicial proceedings and Taiwan’s international standing further reinforced the dynamic dimension of the discipline. Therefore, this Article provides a valuable case study of twentieth century international lawmaking in East Asia.
Keywords: China; Taiwan; governance; international law; statism; pragmatism; civilized nation; Shanghai; East Asia; League of Nations